2010
DOI: 10.1111/j.1438-8677.2009.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of flower bud vigour in the Mediterranean shrub, Cistus albidus L. at advanced developmental stages

Abstract: To better understand aging in perennials, age-related changes in the physiology of leaves and flower buds of the Mediterranean shrub, Cistus albidus L. were evaluated. Two groups of different ages (5 and 10 years old), both at advanced developmental stages but of similar size, were compared. Total plant biomass, biomass produced per apical meristem and levels of cytokinins, abscisic acid and jasmonic acid in leaves and flower buds, as well as flower production, were measured. No differences in plant size, vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The main vitamin E compound in C. albidus seeds was α-tocopherol, whose content was higher in mature plants than the younger ones (Müller et al, 2014). Similarly, seeds of mature plants had higher concentrations of both salicylic acid and jasmonic acid, which was not the case in flowers and leaves, where no concentration differences were observed between the age groups (Oñate and Munné-Bosch, 2010). The adaptability of the species to drought involved an increase in abscisic (ABA) and ascorbic acid (AA) levels, as well as leaf H 2 O 2 concentrations, localized mainly in mesophyll cell walls, xylem vessels, and differentiating sclerenchyma cells (Jubany-Marí et al, 2009).…”
Section: Chemical Analysesmentioning
confidence: 80%
See 1 more Smart Citation
“…The main vitamin E compound in C. albidus seeds was α-tocopherol, whose content was higher in mature plants than the younger ones (Müller et al, 2014). Similarly, seeds of mature plants had higher concentrations of both salicylic acid and jasmonic acid, which was not the case in flowers and leaves, where no concentration differences were observed between the age groups (Oñate and Munné-Bosch, 2010). The adaptability of the species to drought involved an increase in abscisic (ABA) and ascorbic acid (AA) levels, as well as leaf H 2 O 2 concentrations, localized mainly in mesophyll cell walls, xylem vessels, and differentiating sclerenchyma cells (Jubany-Marí et al, 2009).…”
Section: Chemical Analysesmentioning
confidence: 80%
“…The production of phytohormones and vitamins were studied in C. albidus seeds (Müller et al, 2014), leaves, and flowers (Oñate and Munné-Bosch, 2010), in relation to plant maturity. The main vitamin E compound in C. albidus seeds was α-tocopherol, whose content was higher in mature plants than the younger ones (Müller et al, 2014).…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Juvenile shrubs typically do not flower or produce seeds (Bond 2000), and bloom vigor may decrease in older shrubs (Oñate and Munné-Bosch 2010), potentially limiting resources for nectaring butterflies. Dasiphora fruticosa regenerates clonally as well as through recruitment of seedlings (Elkington and Woodell 1963;Lent and Reier 1999).…”
Section: Environment Of Dasiphora Fruticosa As Habitat For Immature Lmentioning
confidence: 99%
“…As perennials age, resource allocation shifts from growth and leaf expansion to reproduction (Bond 2000). Plant age may affect bloom production and vigor (Oñate and Munné-Bosch 2010) and nectar quality and availability (Búrquez and Corbet 1998). Age-dependent nectar quality and quantity potentially can affect butterfly population persistence particularly for those reliant on few or isolated host plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it is still not clear that the reproductive capacity of plants decreases with age. While some studies have shown that the reproductive potential of perennial plants decreases with age (Herrera and Jovani 2010), others indicate that flower production increases with leaf area and specific climatic conditions, irrespective of plant age (Ehlers and Olesen 2004;Oñate and Munné-Bosch 2010).…”
Section: Introductionmentioning
confidence: 99%